The Civilization of Batanghari River: The Relationship between Dharmasraya Temple and Muarajambi Ancient Malay Period in Religious Perspective - Asyhadi Mufsi Sadzali; Wulan Resiyani; Yundi Fitrah (Proceeding International Conference on Malay Identity, 2021)
Abstract: Throughout the course of human civilization since prehistoric times, rivers have been the main determinant in choosing residential locations, including the Batanghari River area. Archaeological research data showed that the distribution of ancient settlements follows the pattern of the Batanghari watershed from upstream to downstream to the estuary. In the upstream area there is the Dharmasraya temple area, and in the downstream there is the Muarajambi temple area, both of which became the center of ancient Malay civilization between the VII and XIV centuries AD. This phenomenon raised a fundamental question, whether the two were related or connected, especially related to religion or religious background? This question was answered by a qualitative research method with a social archeology approach with stages of data collection, data analysis, and data interpretation. The theory of " Entanglemen of humans and things " states by Ian Hodder (2011) is used as a conceptual basis in the analysis and interpretation stage, which then result in the assumption that there was a religious relationship between the Dhamasraya temple in the upstream and the Muarajambi temple in the downstream, both of which were set in Mahayana Tantrayana Buddhism. There were also differences, upstream religion was in the form of tantrayana a widya or left-wing, while downstream was tantrayana widya or right-wing. The similarities and differences were influenced by its position in the Batanghari watershed area. Keywords: Civilization, Batanghari River, Ancient Malay.